Democratization of data visualization: A case study of an interactive urban intervention - Baeza Manteiga, Neily; Arantes Venancio, Tâmer; Andrade Vivas, Thais; Tiradentes Souto, Virgínia; Silva, Tiago Barros Pontes e (InfoDesign, 2024)
Starting from the premise that popular participation is essential for the exercise of democracy, this study explores the potential of a collaborative process of data production and visualisation through an urban intervention in the public transport system of the Brazilian capital. Based on the observed experiences, it was found that collaborative practises such as urban interventions are not common, but they enabled the participation of people of different ages and backgrounds. The participants felt connected to the topic, understood the steps to follow and collaborated not only in the creation of a data visualisation but also in the reflection and interpretation of the information collected. It was concluded that the use of participatory processes can make it possible to gather valuable information about what people expect from a particular public service and also to put them in the role of active subjects who interpret, question and respond to the society in which they live.